2011
DOI: 10.1061/(asce)hy.1943-7900.0000427
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methods Used in 1D Models for Computing Bed-Load Transport in a Large River: The Danube River in Slovakia

Abstract: Comprehensive measurements of bedload sediment transport through a section of the Danube River, located approximately 70km downstream from Bratislava, Slovakia, are used to assess the accuracy of bedload formulae implemented in 1D modelling. Depending on water discharge and water level, significant variations in the distribution of bedload across the section were observed. It appeared that, whatever the water discharge, the bed shear stress τ is always close to the estimated critical bed shear stress for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Indeed, as observed by (Camenen et al, 2011), large variations of the bed shear stress may be observed throughout the section; and as bedload transport is non linear, one should compute bedload locally to yield a proper estimation of the total bedload transport across the section. This remark is even more important if a variation of the grain size is found throughout the section, as is often observed (Habersack and Geomorphology 139-140 (2012) , 2001;Frings and Kleinhans, 2008).…”
Section: Estimation Of the Bed Shear Stressmentioning
confidence: 98%
“…Indeed, as observed by (Camenen et al, 2011), large variations of the bed shear stress may be observed throughout the section; and as bedload transport is non linear, one should compute bedload locally to yield a proper estimation of the total bedload transport across the section. This remark is even more important if a variation of the grain size is found throughout the section, as is often observed (Habersack and Geomorphology 139-140 (2012) , 2001;Frings and Kleinhans, 2008).…”
Section: Estimation Of the Bed Shear Stressmentioning
confidence: 98%
“…1 shows the location of the study reach. According to Camenen et al (2011), the Danube River has experienced a dramatic change due to flood protection projects, the construction of navigation channels, and instream structures in the upstream reach of the river. As a result, the downstream reach of the SlovakHungarian Danube River has become degraded.…”
Section: Application To the Gravel-bed Rivermentioning
confidence: 99%
“…As a result, the downstream reach of the SlovakHungarian Danube River has become degraded. To study the impact of the hydropower plant, Camenen et al (2011) made extensive measurements of the bedload with a basket-type bedload sampler. The sampling point of the bedload is located about 11 km downstream from the gauging station.…”
Section: Application To the Gravel-bed Rivermentioning
confidence: 99%
See 2 more Smart Citations